2010
DOI: 10.1007/s12042-010-9055-0
|View full text |Cite
|
Sign up to set email alerts
|

Opuntia and Other Cacti: Applications and Biotechnological Insights

Abstract: The cactus family is unusual among tropical plants. Cacti, known for their minimum water requirement, have been grown extensively in arid lands, for food, feeds and medicinal and therapeutic uses.Several food products have cacti as a main ingredient. Cacti biochemical analysis substantiate the high nutritive value of this plant family. Tissue cultures, including micropropagation, callus, and cell suspension cultures have been established for numerous cacti species. Genetic engineering has opened opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 85 publications
1
39
0
3
Order By: Relevance
“…Micropropagation can be a useful tool for solving or overcoming these problems because sexual propagation is replaced by vegetative propagation cycles, which usually maintain the genetic fidelity of the starting material (cloning) and shorten the propagation period (usually from several months to a few weeks) (Malda et al, 1999b). In general, artificial growth media provide good conditions for either in vitro seed germination of almost all cactus species or for their micropropagation under aseptic conditions and controlled temperature, light and nutrition regimes (Shedbalkar and Adki, 2010). In some cases, full-strength MS (Murashige and Skoog, 1962) medium can inhibit or delay seed germination of cactus species (Lema-Rumińska and Kulus, 2012;Lema-Rumińska and Kulus, 2014).…”
Section: In Vitro Propagationmentioning
confidence: 99%
“…Micropropagation can be a useful tool for solving or overcoming these problems because sexual propagation is replaced by vegetative propagation cycles, which usually maintain the genetic fidelity of the starting material (cloning) and shorten the propagation period (usually from several months to a few weeks) (Malda et al, 1999b). In general, artificial growth media provide good conditions for either in vitro seed germination of almost all cactus species or for their micropropagation under aseptic conditions and controlled temperature, light and nutrition regimes (Shedbalkar and Adki, 2010). In some cases, full-strength MS (Murashige and Skoog, 1962) medium can inhibit or delay seed germination of cactus species (Lema-Rumińska and Kulus, 2012;Lema-Rumińska and Kulus, 2014).…”
Section: In Vitro Propagationmentioning
confidence: 99%
“…To the best of our knowledge, there is no published record on the traditional use of Opuntia ficus-indica to treat gonorrhoea and hypertension in South Africa. However, compound with resemblance to activities of sarsaparilla vine (Smilax officinalis), which might be useful in the treatment of gonorrhoea, has been isolated from Opuntia ficus-indica (Shedbalkar et al, 2010). Furthermore, Chauhan et al (2010) also demonstrated various activities of this species including antihypertensive activities.…”
Section: Conservation Of Agricultural Resources Act (Cara) Listed Spementioning
confidence: 99%
“…Opuntia crop could be established in drought regions of many countries, including Africa and India (Ennouri et al 2006). Germplasm conservation, genetic engineering and tissue culture are key strategies in successful implementation of this vision (Shedbalkar et al 2010;Zoghlami et al (2012). Axillary-branching micropropagation technique for high degree of clonal fidelity and conservation of interesting genetic resources was recommended.…”
Section: Strategies To Reduce Postharvest Loss and Rolementioning
confidence: 99%